Analysis of Procedures for Providing Working Capital Loans at the Head Office of PT. Bank Sulawesi Selatan & Sulawesi Barat - Besse Sarifah; Haedar Akib; Herlina Sakawati (Public Resource Innovation Management and Excellence, 2025)
Analysis of Procedures for Providing Working Capital Loans at the Head Office of PT. Bank Sulawesi Selatan & Sulawesi Barat This research and writing aims to identify and explain: 1) Know the procedures for granting working capital loans at the Head Office of PT. Bank Sulselbar, 2) Knowing the supporting and inhibiting factors for granting working capital loans at the Head Office of PT. Sulselbar Bank. To achieve this goal, researchers used data collection techniques through observation, interviews, and documentation. The data that has been obtained from the research results are processed using descriptive qualitative where descriptive qualitative research is a formulation of the problem that guides research to explore or photograph social situations which will be thoroughly, broadly and in-depth examined to find out the Analysis of Procedures for Granting Working Capital Loans at the Head Office of PT . South Sulawesi & West Sulawesi Banks. Informants of this study amounted to 4 people. The research results show that: (1) PT. Bank Sulselbar in providing Working Capital Loans (KMK) goes through several stages, such as the debtor preparing application files, KTP, KK, Business Legality Files then checking B.I checking then, doing On The Spot (OTS), after that the credit decision stage which contains approval there will be the provision of working capital credit according to the application submitted, then the credit disbursement stage is notifying the prospective debtor that the KMK application has received approval or a decision on the date of disbursement, preparing a letter of acknowledgment of debt, filling out the KMK receipt, and signing the KMK disbursement agreement. (2) The determinant factors that influence the provision of working capital loans are supporting factors consisting of third party funds and the influence of CAR on credit. The inhibiting factors are ignorance of the flow and procedures by prospective creditors.